2021
DOI: 10.3390/nu13072161
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acid Load and Its Interaction with IGF1 (rs35767 and rs7136446) and IL6 (rs1800796) Polymorphisms on Metabolic Traits among Postmenopausal Women

Abstract: The objective of this study was to explore the effects of dietary acid load (DAL) and IGF1 and IL6 gene polymorphisms and their potential diet–gene interactions on metabolic traits. A total of 211 community-dwelling postmenopausal women were recruited. DAL was estimated using potential renal acid load (PRAL). Blood was drawn for biochemical parameters and DNA was extracted and Agena® MassARRAY was used for genotyping analysis to identify the signalling of IGF1 (rs35767 and rs7136446) and IL6 (rs1800796) polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Concerning the association between DAL and IGF-1 concentration, research is too scarce. In a study, Lim et al did not find any interaction effects between DAL and IGF-1 ( 65 ). Moreover, several relatively archaic studies have indicated that NH4Cl-induced metabolic acidosis reduces IGF-1 ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 93%
“…Concerning the association between DAL and IGF-1 concentration, research is too scarce. In a study, Lim et al did not find any interaction effects between DAL and IGF-1 ( 65 ). Moreover, several relatively archaic studies have indicated that NH4Cl-induced metabolic acidosis reduces IGF-1 ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 93%
“…Diets that yield a high DAL are naturally abundant in protein [ 81 ]. Although a 2021 study by Lim et al did not support an interaction effect between DAL and IGF-1 [ 82 ], multiple other studies have shown that IGF-1 increases with a high-protein diet [ 83 , 84 ]. The combined effects of hyperinsulinemia and elevated IGF-1 levels could thus be a significant contributor to cell proliferation in DAL-induced cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the obtained sample size of 211 was adequate to test the study hypotheses. The methodology of this study has been previously published elsewhere ( 33 35 ). Written informed consent was obtained from all respondents prior to enrolment in the study.…”
Section: Methodsmentioning
confidence: 99%